IPTEKS MEMBANDINGKAN PROFITABILITAS ANTAR PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - Hongkong, Hendra (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2019)
The valuation of financial performance is an important factor on firms commonly and it also have important role for public firms. The valuation of financial performance of firms also gives important information for investors in term to invest their funds for firms. An indicator of financial performance which is most attracts the investors is profitability. The result of applied science with paired samples t test shows that consumer goods industry has better profitability (proxied by return on assets) relative to other industries.